Inequality in Chile Before the First Globalization: An Approach Derived from Agricultural Market Income, 1830s-1850s - Navarrete-Montalvo, J; Llorca-Jana, M; Araya-Valenzuela, R (Universidad de Murcia, 2018)
This article assesses agricultural market income inequality by examining three untapped comprehensive agricultural censuses of all of Chile, undertaken in 1834, 1838 and 1852. Since there had been no Chilean income inequality measurements prior to 1860, this is a novel contribution. Given Chile s great dependence on the agricultural sector during the pre-industrial period of the 1830s to 1850s, measures of agricultural market income inequality can safely be taken as a proxy for total income inequality. This study found that agricultural market income inequality was extremely high during the first decades after Chilean independence. Gini coefficients for agricultural market income among landowners were 0.75, 0.75 and 0.79 for 1834, 1838 and 1852 respectively, while the figures for the entire rural Chilean population, including the landless, were 0.79, 0.87, and 0.89. Around 85% of the population did not own any land and for an unskilled labourer to rent a plot of 1,500 hectares in 1834 cost 3.3 years of wages, and annual wages of 11.3 in 1838. In a conclusion that is at odds with previous historiographical findings, our data suggest that inequality in Chile was very high and had begun to increase decades before the first globalization. © 2014 SEHA.